Effects of melatonin on follicular atresia and granulosa cell apoptosis in the porcine. Issue 8 (21st July 2016) - He, Yamei; Deng, Honghui; Jiang, Zhongliang; Li, Qingwang; Shi, Meihong; Chen, Huali; Han, Zengsheng
SUMMARY: The accumulation of reactive oxygen species is detrimental to the health of the ovarian follicle. The protective, antioxidant properties of melatonin, an endogenous component of porcine follicular fluid, on apoptosis of granulosa cells were evaluated in this study. Porcine granulosa cells from medium‐sized (3–5 mm), healthy follicles were cultured in serum‐free conditions with melatonin (0, 0.01, 0.1, 1.0, 10, and 100 ng/mL) with or without its receptor antagonist, luzindole, followed by evaluation of apoptotic markers in the treated cells. Results revealed that endogenous, intrafollicular melatonin concentration decreased as follicular atresia progressed, whereas the percentage of apoptotic granulosa cells increased. Spontaneous apoptosis of granulosa cells, triggered by serum deprivation in vitro, was remarkably blocked by melatonin (1.0 ng/mL melatonin, 32.7 ± 0.5%, vs. control, 47.0 ± 1.0%; P < 0.05). Treatment with 1.0 ng/mL of melatonin also significantly elevated MT2, SOD1, and GPX4 while lowering FASL, CHOP, and GRP78 mRNA abundance compared to the untreated control. The anti‐apoptotic effect and some changes of apoptotic‐relevant genes in granulosa cells invoked by melatonin supplementation were markedly blocked by luzindole, suggesting that melatonin could prevent the apoptosis of porcine granulosa cells during follicular atresia via its membrane receptors and its free‐radical‐scavenging activity. These findings provide new insights into the regulatory mechanism of melatonin in follicular atresia‐related functions. Mol. Reprod. Dev. 83: 692–700, 2016 © 2016 Wiley Periodicals, Inc .